Neuroscience-based nomenclature (NbN): the Portuguese version of the new classification for psychopharmacological drugs - José Carlos Fernandes Galduróz; Aleksander Roberto Zampronio; Maria Aparecida Barbato Frazão Vital; Paulo Clemente Sallet; Joseph Zohar; Roberto Andreatini (Trends in Psychiatry and Psychotherapy)
Abstract Neuroscience-based nomenclature (NbN) is a proposal to provide a nomenclature based on neuroscience and pharmacology instead of the old disease-based classification. The NbN is based on the mechanism of action and pharmacological target and aims to assist in rational prescription, to reduce stigma, and to increase treatment adherence. Currently, the NbN is endorsed by many psychiatric associations, has been adopted by several relevant journals, and is included in major psychiatry textbooks. Therefore, it is important that the NbN is known to psychiatrists.